Ciało ludzkie i jego udział w szczęściu nieba – koncepcja Pseudo-Dionizego Areopagity wobec poglądów neoplatoników pogańskich - Stępień, Tomasz (Vox Patrum, 2015)
In seventh chapter of his On the Ecclesiastical Hierarchy Pseudo Dionysius the Areopagite treats on the ceremony of burial. While explaining the rites he makes a few remarks on the Christian understanding of the body and its fate after death, and how it is inconsistent with some pagan views on the matter. He discusses several opposite statements of the complete disintegration of the body, metempsychosis and seeing the life of the body after death exactly like the life on earth (On the Ecclesiastical Hierarchy VII 3, 1). This polemic is pointed against Neoplatonic philosophers who held such opinions, and to understand the difference between pagan and Christian view on the matter, the second part of the article considers the Neoplatonic view of the life after death. At Neoplatonic schools there were a different opinions of whether the embodiment is good or rather damaging to the intellectual soul. Philosophers like Plotinus and Porphyry explained descend of the soul as being evil, while Iamblichus and Damaskios thought otherwise. However there were points in which Neoplatonics were completely in agreement. All of them admitted that the happiness of the soul after death is possible only without the material body, and that the soul can reincarnate. Analysis of Neoplatonic view shows that the negative approach to the body is not the feature that could be ascribed to all Late Greek philosophers. Pseudo-Dionysius sees the problem in the Christian perspective. The soul at the moment of death does not loose completely the connection with the body and thus death does not mean the dissolution of the substance. However the new body that will be given to believers after resurrection will not be exactly the same with the earthly one.